Rubber composition and method for producing same
By using hypochlorous acid oxidized cellulose in rubber and undergoing anionic modification treatment, the problem of poor affinity and dispersion of nanocellulose in rubber is solved, and a significant increase in strength is achieved, especially in stretching In terms of strength, the preparation process is simplified.
Patent Information
- Application Number
- CN202380038951.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-05-09
- Publication Date
- 2024-12-20
AI Technical Summary
The poor affinity and dispersion of nanocellulose in existing rubbers lead to the inability to fully exert durability and rigidity in the reinforcement material. The preparation process of existing grafted cellulose fibers is complicated and requires simplified operation.
Nanocellulose obtained by oxidizing cellulose with hypochlorous acid or its salt is used, and anionic modification and grafting treatment are performed thereon to form nanocellulose with anionic modification group, thereby improving the tensile strength of the rubber.
The rubber composition obtained by this method significantly improves the strength of the rubber, especially in terms of tensile strength, and has a relatively simple preparation process and high safety.
Smart Images

Figure CN119173569A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a rubber composition and a method for producing the same. Background Art
[0002] In recent years, rubber that is compounded with reinforcing materials to increase strength has been widely used as a lightweight and high-strength material. In recent years, research on the use of plant fibers as resin reinforcing materials has continued to make progress. Plant fibers are not artificially synthesized, but are used after the fibers of plant origin are loosened. Since plant fibers hardly remain as ash during combustion, there will be no problems such as the treatment of ash in incinerators and landfill treatment. Therefore, research on the use of plant fibers as resin reinforcing materials is underway, especially the use of nanocellulose that defibrates plant fibers to the nanometer level.
[0003] As a type of nanocellulose, nanocellulose derived from oxides obtained by oxidizing raw cellulose with hypochlorous acid or its salts is known. For example, Patent Document 1 describes a method for producing nanocellulose, which includes the steps of oxidizing a cellulose-based raw material using hypochlorous acid or its salts having an effective chlorine concentration of 14 to 43% by mass to produce oxidized cellulose, and defibrillating the oxidized cellulose to nanosize it. In addition, Patent Document 2 discloses a method for producing nanocellulose, which includes the steps of: using hypochlorous acid or its salts having an effective chlorine concentration of 6% to 14% by mass, while adjusting the pH to a range of 5.0 to 14.0, subjecting the cellulose-based raw material to an oxidation reaction, and defibrillating the oxidized cellulose to nanosize it.
[0004] Although cellulose fibers are sometimes used as reinforcing materials to improve the strength of rubber, when cellulose fibers are used as rubber reinforcing materials, the composite material of hydrophilic cellulose and hydrophobic rubber has poor affinity and dispersibility for the rubber and cannot exert sufficient durability and rigidity. Therefore, Patent Document 3 describes a rubber composition, characterized in that in order to improve the affinity and dispersibility of nanocellulose in the rubber component, in the rubber composition containing cellulose nanofibers in the rubber component, the cellulose fibers are composite cellulose fibers obtained by graft polymerization of monomers or polymers.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2018 / 230354
[0008] Patent Document 2: International Publication No. 2020 / 027307
[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 2009-263417 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] By incorporating nanocellulose into rubber, a reinforcing effect on the rubber can be expected, but it is still desired to further increase the strength of the rubber.
[0012] Although Patent Documents 1 and 2 describe nanocellulose derived from an oxide obtained by oxidizing raw material cellulose with hypochlorous acid or a salt thereof as nanocellulose, they do not specifically disclose compounding the nanocellulose with rubber.
[0013] Patent Document 3 describes a cellulose fiber obtained by blending a free radical initiator with cellulose to generate free radicals in the cellulose and graft polymerization. In the method for obtaining the grafted cellulose fiber of Patent Document 3, since the functional groups of cellulose are all hydroxyl groups, it is necessary to add a free radical initiator to a specific dispersion medium in order to generate free radicals. Therefore, a method is required that can graft the cellulose fiber by a simpler operation than the grafted cellulose fiber of Patent Document 3 and effectively obtain a rubber composition.
[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a rubber having excellent strength. Another object of the present invention is to effectively provide a rubber having excellent strength.
[0015] Solutions for solving problems
[0016] The present inventors have conducted intensive research and found that the strength of rubber, especially tensile strength, can be improved by using nanocellulose derived from an oxide obtained by oxidizing a cellulose-based raw material with hypochlorous acid or its salt as a rubber material, thereby completing the present invention. In addition, the present inventors have conducted intensive research and found that a rubber composition obtained by grafting a rubber component onto nanocellulose having an anionic modifying group can effectively improve the strength of rubber and is excellent in strength, especially tensile strength, thereby completing the present invention.
[0017] According to the present invention, the following means are provided. [1]
[0019] A rubber composition comprising nanocellulose and a rubber component,
[0020] The nanocellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound. [2]
[0022] A rubber composition comprising nanocellulose and a rubber component,
[0023] The nanocellulose has an anionic modified group,
[0024] The rubber component is grafted onto the nanocellulose. [3]
[0026] A rubber composition comprising nanocellulose and a rubber component,
[0027] The nanocellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and substantially does not contain an N-oxyl compound.
[0028] The rubber component is grafted onto the nanocellulose. [4]
[0030] A rubber obtained by crosslinking the rubber composition according to any one of [1] to [3]. [5]
[0032] A method for producing a rubber composition, wherein the rubber composition comprises nanocellulose and a rubber component.
[0033] The manufacturing method comprises the steps of: stirring a mixture containing oxidized cellulose and a material other than the nanocellulose of the rubber composition, defibring the oxidized cellulose, and obtaining the rubber composition;
[0034] The oxidized cellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound. [6]
[0036] A method for producing a rubber composition, wherein the rubber composition comprises nanocellulose and a rubber component.
[0037] The manufacturing method comprises the following steps: stirring oxidized cellulose, defibrating the oxidized cellulose, and continuously adding materials other than the nanocellulose of the rubber composition to obtain the rubber composition,
[0038] The oxidized cellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound. [7]
[0040] The production method according to [5] or [6], further comprising the step of grafting the nanocellulose onto the rubber component. [8]
[0042] A rubber additive comprising nanocellulose,
[0043] The nanocellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound. [9]
[0045] A rubber additive comprising oxidized cellulose,
[0046] The oxidized cellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound.
[10]
[0048] A composite nanocellulose comprising a rubber component and nanocellulose,
[0049] The nanocellulose has an anionic modified group,
[0050] The rubber component is grafted to the nanocellulose.
[11]
[0052] A composite nanocellulose comprising a rubber component and nanocellulose,
[0053] The nanocellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and substantially does not contain an N-oxyl compound.
[0054] The rubber component is grafted to the nanocellulose.
[12]
[0056] A rubber additive comprising the composite nanocellulose of
[10] or
[11] .
[0057] Effects of the Invention
[0058] According to the present invention, a rubber having excellent strength can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a graph showing the measurement results of the tensile stress / strain of the rubbers of Examples 1 and 2 and Comparative Example 1.
[0060] Figure 2 It is a graph showing the measurement results of tensile stress / strain of the rubbers of Examples 3 to 5 and Comparative Examples 2 to 3. DETAILED DESCRIPTION
[0061] In this specification, oxidized cellulose refers to an oxide of a cellulose-based raw material before defibration.
[0062] In this specification, nanocellulose refers to an oxide of a fibrillated cellulose-based raw material.
[0063] In this specification, composite nanocellulose refers to nanocellulose grafted with a rubber component.
[0064] [Rubber composition: first aspect]
[0065] A rubber composition as one aspect of the present invention comprises nanocellulose and a rubber component, wherein the nanocellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and substantially contains no N-oxyl compound. This rubber composition is also referred to as the rubber composition of the first aspect.
[0066] The rubber composition of the present invention refers to the rubber composition before crosslinking as long as it at least comprises nanocellulose and rubber component. The rubber composition of the present invention, when the rubber composition is made into the first rubber composition, can also be further mixed with other rubbers to make the second rubber composition. That is, the rubber composition of the present invention can be used as a masterbatch, for mixing with other rubbers, rubber components and obtaining rubber.
[0067] According to the rubber composition of the first aspect, a rubber having excellent strength can be obtained. The reason for this is not clear, but the following reasons are generally considered.
[0068] Nanocellulose is obtained through fibrillation, and fibrillation is carried out by cutting off the hydrogen bonds between cellulose microfibrils. In the oxidation treatment using hypochlorous acid or its salt, it is believed that as oxidation proceeds, the degree of polymerization of microfibrils decreases (i.e., the shortening of cellulose molecular chains). Therefore, it can be believed that, by oxidation treatment, the number of hydrogen bonds to be cut off by fibrillation in microfibrils is reduced, and the amount of carboxyl groups is increased by oxidation, thereby strengthening the repulsion between microfibrils, thereby improving the dispersion stability of the obtained nanocellulose. It is believed that this dispersion stability is also brought into play in the rubber component, thereby improving the strength, particularly tensile strength of the rubber.
[0069] <<Nanocellulose in the first aspect>>
[0070] The nanocellulose in the first aspect refers to an oxide obtained by oxidizing a cellulose-based raw material with hypochlorous acid or a salt thereof, that is, nanocellulose obtained by micronizing oxidized cellulose obtained by oxidizing a cellulose-based raw material with hypochlorous acid or a salt thereof.
[0071] <Oxidized cellulose in the first aspect>
[0072] The oxidized cellulose in the first aspect is oxidized cellulose obtained by oxidizing a cellulose-based raw material with hypochlorous acid or a salt thereof. Here, the oxidized cellulose may also be referred to as an oxide of a cellulose-based raw material, and includes fibrous cellulose obtained by oxidizing a cellulose-based raw material with hypochlorous acid or a salt thereof. The oxidized cellulose in the first aspect includes an oxide of a cellulose-based raw material obtained with hypochlorous acid or a salt thereof.
[0073] It should be noted that the main component of plants is cellulose, and bundles of cellulose molecules are called cellulose microfibrils. The cellulose in the cellulose-based raw material may also be contained in the form of cellulose microfibrils.
[0074] The oxidized cellulose in the first aspect contains a carboxyl group, but the carboxyl group may be in the H form (-COOH) or in the salt form. The type of salt is not particularly limited, and examples thereof include alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as calcium salts and barium salts; other metal salts such as magnesium salts and aluminum salts; ammonium salts and organic amine salts.
[0075] The oxidized cellulose in the first aspect is obtained by oxidizing a cellulose-based raw material with hypochlorous acid or a salt thereof, and no N-oxyl compound such as 2,2,6,6-tetramethylpiperidin-1-oxyl (hereinafter also referred to as TEMPO) is used in the oxidation. Therefore, the oxidized cellulose in the first aspect does not substantially contain an N-oxyl compound. Therefore, the above-mentioned oxidized cellulose sufficiently reduces the impact of N-oxyl compounds on the environment and human body, and is highly safe. Here, in this specification, the oxidized cellulose "does not substantially contain an N-oxyl compound" means that no N-oxyl compound is used when producing the oxidized cellulose, and means that the oxidized cellulose does not contain an N-oxyl compound at all, or the content of the N-oxyl compound (i.e., the amount of nitrogen derived from the N-oxyl compound) is 2.0 mass ppm or less, preferably 1.0 mass ppm or less relative to the total amount of the oxidized cellulose. In addition, when the amount of nitrogen derived from the N-oxyl compound is preferably 2.0 mass ppm or less, and more preferably 1.0 mass ppm or less, based on the amount of increase from the cellulose-based raw material, it also means "does not substantially contain an N-oxyl compound". The amount of nitrogen derived from the N-oxyl compound can be measured by a known means. As a known means, there is a method using a trace total nitrogen analyzer (for example, manufactured by Nitto Seiko Analytech Co., Ltd., device name: TN-2100H).
[0076] (Carboxyl amount)
[0077] The carboxyl group content of the oxidized cellulose in the first aspect is preferably 0.20 to 2.0 mmol / g. When the carboxyl group content is 0.20 mmol / g or more, sufficient fibrillation properties can be imparted to the oxidized cellulose. Thus, even if the fibrillation treatment is carried out under mild conditions, a nanocellulose-containing pulp with uniform quality can be obtained, and the viscosity stability and operability of the pulp can be improved. On the other hand, when the carboxyl group content is 2.0 mmol / g or less, excessive decomposition of cellulose during the fibrillation treatment can be suppressed, and nanocellulose with a small ratio of granular cellulose and uniform quality can be obtained. It is believed that the dispersibility is thereby improved. From such a viewpoint, the carboxyl group content of the oxidized cellulose is more preferably 0.30 mmol / g or more, further preferably 0.35 mmol / g or more, further preferably 0.40 mmol / g or more, further more preferably 0.42 mmol / g or more, more preferably 0.50 mmol / g or more, further preferably greater than 0.50 mmol / g, and further more preferably 0.55 mmol / g or more. The upper limit of the amount of carboxyl groups may be less than 2.0 mmol / g, may be less than 1.5 mmol / g, may be less than 1.2 mmol / g, may be less than 1.0 mmol / g, and may be less than 0.9 mmol / g. The preferred range of the amount of carboxyl groups can be determined by appropriately combining the above upper and lower limits. The amount of carboxyl groups in the oxidized cellulose is more preferably 0.30 mmol / g or more and less than 2.0 mmol / g, further preferably 0.35 to 2.0 mmol / g, further preferably 0.35 to 1.5 mmol / g, further more preferably 0.40 to 1.5 mmol / g, further more preferably 0.50 to 1.2 mmol / g, further preferably greater than 0.50 mmol / g and less than 1.2 mmol / g, further more preferably 0.55 to 1.0 mmol / g.
[0078] It should be noted that the carboxyl group amount (mmol / g) is a value calculated using the following formula based on the amount of sodium hydroxide (a) consumed in the neutralization stage of a weak acid whose conductivity changes relatively slowly, after adding a 0.1 M hydrochloric acid aqueous solution to an aqueous solution of oxidized cellulose and water until the pH reaches 2.5, and then dropping a 0.05 N sodium hydroxide aqueous solution, and measuring the conductivity until the pH reaches 11.0. The details are as described in the examples described later. The carboxyl group amount can be adjusted by changing the reaction time, reaction temperature, pH of the reaction solution, etc. of the oxidation reaction.
[0079] Carboxyl group amount = a (ml) × 0.05 / oxidized cellulose mass (g)
[0080] The above-mentioned oxidized cellulose can be obtained by oxidizing a cellulose-based raw material under the condition that the effective chlorine concentration of hypochlorous acid or its salt in the reaction system is relatively high (for example, 6% to 43% by mass). In addition, the above-mentioned oxidized cellulose can also be produced by appropriately controlling reaction conditions such as the effective chlorine concentration, the pH during the reaction, the reaction temperature, etc. The oxidized cellulose thus obtained preferably has a structure in which at least two hydroxyl groups in the pyranose glucose ring constituting the cellulose are oxidized, and more specifically, preferably has a structure in which the hydroxyl groups at the 2nd and 3rd positions in the pyranose glucose ring are oxidized to introduce dicarboxyl groups. In addition, the hydroxyl group at the 6th position of the pyranose glucose ring in the oxidized cellulose is preferably not oxidized and remains a hydroxyl group. It should be noted that the position of the carboxyl group in the pyranose glucose ring of the oxidized cellulose can be controlled by solid 13 C-NMR spectrum was used for analysis.
[0081] Rayon has the same chemical structure as cellulose, and its oxide (oxidized rayon) is water-soluble. 13 C-NMR measurement, a carbon peak attributable to the carboxyl group was observed at 165-185 ppm. In one embodiment of the oxidized cellulose or nanocellulose obtained by oxidizing a cellulose-based raw material with hypochlorous acid or its salt used in the present invention, two signals appeared in this chemical shift range. Furthermore, by solution two-dimensional NMR measurement, it can be determined that the carboxyl group is introduced at the 2-position and the 3-position.
[0082] Solid oxidized cellulose or nanocellulose obtained by oxidizing a cellulose-based raw material with hypochlorous acid or its salt 13 In C-NMR, when the amount of carboxyl introduced is large, two signals appear at 165-185 ppm, and when the amount of carboxyl introduced is small, a very broad signal may appear. From the results of oxidized rayon, it can be seen that the signals of the carboxyl carbon introduced at the 2nd and 3rd positions are close, and in the solid state with lower resolution, the signals of the carboxyl carbon introduced at the 2nd and 3rd positions are close. 13 In C-NMR, the separation of these two signals is insufficient. Therefore, when the amount of carboxyl groups introduced is small, a broad signal is observed. 13 In the C-NMR spectrum, by evaluating the development of the peak appearing at 165 to 185 ppm, it was confirmed that the carboxyl groups were introduced at the 2-position and the 3-position.
[0083] That is, in solid 13 Draw a baseline at the peak in the range of 165ppm to 185ppm in the C-NMR spectrum, and after calculating the total area value, calculate the ratio of the area values of the two peaks obtained by vertically dividing the area value at the peak top (large area value / small area value). When the ratio of the peak area values is greater than 1.2, it can be said to be a broad peak.
[0084] In addition, the presence or absence of the above-mentioned broad peak can be judged based on the ratio of the length L of the baseline in the range of 165ppm to 185ppm to the length L' of the vertical line from the peak top to the baseline. That is, when the ratio L' / L is greater than 0.1, it can be judged that a broad peak exists. The above-mentioned ratio L' / L can be greater than 0.2, greater than 0.3, greater than 0.4, or greater than 0.5. The upper limit of the ratio L' / L is not particularly limited, and can generally be less than 3.0, less than 2.0, or less than 1.0.
[0085] In addition, the structure of the above-mentioned pyranose glucose ring can be analyzed and determined according to the method described in Sustainable Chem. Eng. 2020, 8, 48, 17800-17806.
[0086] (Degree of Polymerization)
[0087] The polymerization degree of the oxidized cellulose in the first aspect is preferably 600 or less. When the polymerization degree of the oxidized cellulose is greater than 600, there is a tendency that a large amount of energy is required for defibration, and sufficient defibration is not exhibited, the dispersibility of the pigment is reduced, and there is even a tendency to cause a decrease in optical density. In addition, when the polymerization degree of the oxidized cellulose is greater than 600, since the amount of oxidized cellulose that is not fully defibrated increases, when the nanocellulose obtained by micronizing it is dispersed in the dispersion medium, sometimes light scattering increases, and the dispersibility decreases. In addition, there is a tendency that the size of the obtained nanocellulose is uneven and the quality is uneven. Therefore, when nanocellulose is made, there is a tendency that the viscosity of the dispersant becomes higher. From the viewpoint of easy defibration, the lower limit of the polymerization degree of the oxidized cellulose is not particularly set. However, when the polymerization degree of the oxidized cellulose is less than 50, the proportion of granular rather than fibrous cellulose will increase, and the function as a dispersant may be reduced. From the above viewpoints, the polymerization degree of the oxidized cellulose is preferably in the range of 50 or more and 600 or less.
[0088] The degree of polymerization of oxidized cellulose is more preferably 580 or less, further preferably 560 or less, further preferably 550 or less, further preferably 500 or less, further preferably 450 or less, further more preferably 400 or less. The lower limit of the degree of polymerization is more preferably 60 or more, further preferably 70 or more, further preferably 80 or more, further preferably 90 or more, further preferably 100 or more, further more preferably 110 or more, and particularly preferably 120 or more. The preferred range of the degree of polymerization can be determined by appropriately combining the above upper and lower limits. The degree of polymerization of oxidized cellulose is more preferably 60 to 600, further preferably 70 to 600, further preferably 80 to 600, further more preferably 80 to 550, further preferably 80 to 500, further preferably 80 to 450, and particularly preferably 80 to 400.
[0089] It should be noted that the degree of polymerization of oxidized cellulose can be adjusted by changing the reaction time, reaction temperature, pH, and effective chlorine concentration of hypochlorous acid or its salt during the oxidation reaction. Specifically, when the degree of oxidation is increased, the degree of polymerization tends to decrease. Therefore, in order to reduce the degree of polymerization, for example, methods of increasing the oxidation reaction time and / or reaction temperature can be cited. As another method, the degree of polymerization of oxidized cellulose can be adjusted by the stirring conditions of the reaction system during the oxidation reaction. For example, under the condition that the reaction system is sufficiently uniform using a stirring blade, the oxidation reaction proceeds smoothly and the degree of polymerization tends to decrease. On the other hand, under the condition that the stirring of the reaction system is likely to become insufficient, such as stirring with a stirrer, the reaction tends to become uneven, and it is difficult to sufficiently reduce the degree of polymerization of oxidized cellulose. In addition, the degree of polymerization of oxidized cellulose also tends to vary with the selection of cellulose-based raw materials. Therefore, the degree of polymerization of oxidized cellulose can be adjusted by selecting cellulose-based raw materials. It should be noted that in this specification, the degree of polymerization of oxidized cellulose is the average degree of polymerization (viscosity average degree of polymerization) measured by the viscosity method. The degree of polymerization of oxidized cellulose can be specifically measured by the following [Determination of viscosity average degree of polymerization].
[0090] [Determination of viscosity average degree of polymerization]
[0091] Oxidized cellulose is added to an aqueous sodium borohydride solution adjusted to pH 10 and subjected to reduction treatment at 25°C for 5 hours. The amount of sodium borohydride is 0.1 g relative to 1 g of oxidized cellulose. After the reduction treatment, solid-liquid separation and water washing are performed by suction filtration, and the obtained oxidized cellulose is freeze-dried. 0.04 g of dried oxidized cellulose is added to 10 ml of pure water and stirred for 2 minutes, and then 10 ml of 1M copper ethylenediamine solution is added to dissolve it. Then, the flow time of the blank solution and the flow time of the cellulose solution are measured at 25°C using a capillary viscometer. The relative viscosity (η) is calculated in turn from the flow time of the blank solution (t0), the flow time of the cellulose solution (t), and the concentration of the oxidized cellulose (c [g / ml]) as follows: r ), specific viscosity (η sp ) and intrinsic viscosity ([η]), and the degree of polymerization (DP) of oxidized cellulose was calculated by the viscosity determination formula.
[0092] η r =η / η0=t / t0
[0093] η sp =η r -1
[0094] [η] = η sp / (100×c(1+0.28η sp ))
[0095] DP = 175 × [η]
[0096] (Method for producing oxidized cellulose in the first aspect)
[0097] The oxidized cellulose in the first aspect can be produced by oxidizing a cellulose-based raw material with hypochlorous acid or a salt thereof.
[0098] There are no particular restrictions on the cellulose raw material, as long as it is a material mainly composed of cellulose, and examples thereof include pulp, natural cellulose, regenerated cellulose, and fine cellulose obtained by mechanically treating cellulose for depolymerization. As the cellulose raw material, commercially available products such as crystalline cellulose using pulp as a raw material can be used directly. In addition, unused biomass containing a large amount of cellulose components such as bean dregs and soybean hulls can also be used as a raw material. In addition, in order to make it easier for the oxidant used to penetrate into the raw pulp, the cellulose raw material can be treated with an alkali of an appropriate concentration in advance.
[0099] Specific production methods include, for example, methods described in International Publication Nos. 2022 / 009979 and 2022 / 009980. Oxidized cellulose can also be obtained as a commercial product, for example, Aron Fibro (registered trademark) manufactured by Toagosei Co., Ltd., etc.
[0100] The oxidized cellulose is preferably in the form of a dispersion. The dispersion referred to herein refers to a suspension containing the oxidized cellulose. The dispersion may contain a solvent used in oxidation. In addition, a dispersion medium may be appropriately added to make the oxidized cellulose in the form of a dispersion. Since the oxidized cellulose is a dispersion, it is easy to handle and tends to be easily micronized.
[0101] In the case where the oxidized cellulose in the first aspect is a dispersion, when the total amount of the dispersion is 100 mass%, the amount of the oxidized cellulose is usually in the range of 0.1 mass% to 95 mass%, preferably 1 mass% to 50 mass%, and more preferably 1 mass% to 30 mass%.
[0102] At least a part of the oxidized cellulose in the first aspect in the rubber composition of the present invention is micronized into nanocellulose. The nanocellulose may be the same as the following (nanocellulose).
[0103] <Nanocellulose in the first aspect>
[0104] The nanocellulose in the first aspect is obtained by micronizing oxidized cellulose obtained by oxidizing a cellulose-based raw material with hypochlorous acid or its salt. Here, the oxidized cellulose may be the embodiment described in <Oxidized cellulose in the first aspect>. The nanocellulose in the first aspect may also be said to be derived from oxidized cellulose obtained by oxidizing a cellulose-based raw material with hypochlorous acid or its salt. The nanocellulose in the first aspect includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or its salt.
[0105] Nanocellulose in the first aspect is a general term for cellulose obtained by micronizing cellulose, and includes fine cellulose fibers, cellulose nanocrystals, etc. Fine cellulose fibers are also called cellulose nanofibers (also described as CNF).
[0106] The nanocellulose in the first aspect contains a carboxyl group, but the carboxyl group may be in the H type (-COOH) or in the salt type. The type of salt is not particularly limited, and examples thereof include alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as calcium salts and barium salts; other metal salts such as magnesium salts and aluminum salts; ammonium salts and organic amine salts.
[0107] The nanocellulose in the first aspect is obtained by oxidizing a cellulose-based raw material with hypochlorous acid or a salt thereof, and no N-oxyl compound such as TEMPO is used in the oxidation. Therefore, the nanocellulose in the first aspect does not substantially contain an N-oxyl compound. The definition of nanocellulose "does not substantially contain an N-oxyl compound" is the same as the definition of oxidized cellulose "does not substantially contain an N-oxyl compound" described in <Oxidized cellulose in the first aspect> above.
[0108] (Carboxyl amount)
[0109] The amount of carboxyl groups in the nanocellulose in the first aspect is preferably the same as that described in the above-mentioned <Oxidized cellulose in the first aspect>.
[0110] The carboxyl group content (mmol / g) of nanocellulose can be measured by the same method as the method for measuring the carboxyl group content of oxidized cellulose described above.
[0111] The nanocellulose in the first aspect is a single fiber or an aggregate of this fiber. When nanocellulose includes carboxylated nanocellulose, the aggregate of this fiber includes at least one carboxylated nanocellulose, and preferably carboxylated nanocellulose is the main component. Here, carboxylated nanocellulose is the main component and refers to that the ratio of carboxylated nanocellulose to the total amount of nanocellulose exceeds 50 mass %, preferably exceeds 70 mass %, and more preferably exceeds 80 mass %. The upper limit of the above ratio is 100 mass %, but can be 98 mass %, or can be 95 mass %.
[0112] (Average fiber length)
[0113] The average fiber length of the nanocellulose in the first aspect is preferably 50 to 700 nm, more preferably 50 to 500 nm, further preferably 50 to 300 nm, further preferably 60 to 300 nm, and further more preferably 70 to 200 nm. When the average fiber length exceeds 700 nm, the slurry will become severely thickened and difficult to handle. In addition, when the average fiber length is less than 50 nm, it is difficult to show the viscosity that is a characteristic of nanocellulose.
[0114] (Average fiber width)
[0115] The average fiber width of the nanocellulose in the first aspect is preferably 1 to 200 nm, more preferably 1 to 15.0 nm, more preferably 1 to 10 nm, and further preferably 1 to 5 nm. When the average fiber width is less than 1 nm, it is difficult to show that the strength of the resin containing nanocellulose is improved. In addition, when the average fiber width is greater than 200 nm, when the ink composition is prepared, the jetting stability in inkjet printing is sometimes reduced.
[0116] It should be noted that the average fiber width and the average fiber length are obtained by mixing nanocellulose with water in a manner such that the concentration of nanocellulose is about 1 to 10 ppm, naturally drying the fully diluted cellulose aqueous dispersion on a mica substrate, observing the shape of the nanocellulose using a scanning probe microscope, randomly selecting any number of fibers from the obtained image, and calculating the values by substituting the cross-sectional height of the shape image = fiber width and the perimeter ÷ 2 = fiber length. Image processing software can be used to calculate the average fiber width and the average fiber length. In this case, the conditions for image processing are arbitrary, but depending on the conditions, the calculated values may differ even in the same image. The range of the value difference caused by the conditions is preferably within the range of ±100 nm for the average fiber length. The range of the value difference caused by the conditions is preferably within the range of ±10 nm for the average fiber width.
[0117] (Aspect Ratio)
[0118] In the nanocellulose according to the first aspect, the aspect ratio (average fiber length / average fiber width) represented by the ratio of the average fiber width to the average fiber length is preferably 20 or more and 200 or less.
[0119] It is considered that the dispersibility of nanocellulose is improved and the binding property can be further improved when the aspect ratio is 200 or less. From such a viewpoint, the aspect ratio is more preferably 190 or less, and further preferably 180 or less.
[0120] On the other hand, when the aspect ratio is too low, that is, the shape of the nanocellulose is thick rod-like rather than slender fiber-like, aggregation occurs due to uneven distribution, and there is a tendency for the dispersibility to decrease. Therefore, the aspect ratio is preferably 20 or more, more preferably 30 or more, and further preferably 40 or more.
[0121] The nanocellulose in the first aspect preferably satisfies the following zeta potential and light transmittance.
[0122] (zeta potential)
[0123] The zeta potential of the nanocellulose in the first aspect is preferably below -30 mV. When the zeta potential is below -30 mV (i.e., the absolute value is above 30 mV), the microfibrils can be fully repelled from each other, and nanocellulose with a high surface charge density is easily produced during mechanical fibrillation. As a result, the dispersion stability of the nanocellulose is improved, and when made into a slurry, it can have excellent viscosity stability and operability.
[0124] The lower limit of the zeta potential is not particularly limited, but may usually be -100 mV or higher.
[0125] When the zeta potential is above -100 mV (i.e., the absolute value is below 100 mV), as the oxidation proceeds, the oxidative cutting in the fiber direction tends to be suppressed, so that nanocellulose of uniform size can be obtained, the nanocellulose is stable in water and the dispersibility is enhanced, and the obtained dispersion evenly contains the nanocellulose.
[0126] From the above viewpoints, the zeta potential of nanocellulose is preferably below -35mV, more preferably below -40mV, and further preferably below -50mV. In addition, with regard to the lower limit of the zeta potential, it is preferably above -90mV, more preferably above -85mV, further preferably above -80mV, further preferably above -77mV, further more preferably above -70mV, and further preferably above -65mV. The range of zeta potential can appropriately combine the above lower and upper limits. The zeta potential is preferably above -90mV and below -30mV, more preferably above -85mV and below -30mV, further preferably above -80mV and below -30mV, further more preferably above -77mV and below -30mV, further preferably above -70mV and below -30mV, more preferably above -65mV and below -30mV, and further preferably above -65mV and below -35mV.
[0127] In this specification, the zeta potential is a value measured on a cellulose aqueous dispersion in which nanocellulose and water are mixed and the nanocellulose concentration is 0.1 mass % under the conditions of pH 8.0 and 20° C. Specifically, the zeta potential can be measured under the following conditions.
[0128] 〔Zeta potential measurement〕
[0129] Pure water was added to the dispersion containing nanocellulose to dilute it to a nanocellulose concentration of 0.1%. A 0.05 mol / L sodium hydroxide aqueous solution was added to the diluted nanocellulose aqueous dispersion to adjust the pH to 8.0, and the zeta potential was measured at 20°C using a zeta potentiometer (ELSZ-1000) manufactured by Otsuka Electronics Co., Ltd.
[0130] (Transmittance)
[0131] The nanocellulose dispersion obtained by dispersing the nanocellulose in the first aspect in a dispersion medium has less light scattering of the cellulose fibers and can show high light transmittance. Specifically, the nanocellulose in the first aspect is preferably 95% or more when mixed with water to form a mixed solution with a solid content concentration of 0.1% by mass. The light transmittance is more preferably 96% or more, further preferably 97% or more, and further preferably 99% or more. It should be noted that the light transmittance is a value at a wavelength of 660nm measured using a spectrophotometer. In addition, an aqueous dispersion containing nanocellulose can be used to measure the light transmittance. Specifically, it can be measured under the conditions described below.
[0132] 〔Measurement of light transmittance〕
[0133] An aqueous dispersion of nanocellulose having a solid content concentration of 0.1% by mass was placed in a 10 mm thick quartz cuvette, and the light transmittance at a wavelength of 660 nm was measured using a spectrophotometer (JASCO V-550).
[0134] The zeta potential and light transmittance can be controlled by oxidation using hypochlorous acid or its salts, and in particular, can be controlled by adjusting the reaction time, reaction temperature, stirring conditions, etc. of the oxidation reaction. Specifically, as the reaction time is prolonged and / or the reaction temperature is increased, the oxidation of the surface of the cellulose microfibrils in the cellulose-based raw material proceeds, and due to electrostatic repulsion and osmotic pressure, the repulsion between the fibrils is enhanced, thereby the average fiber width tends to become smaller. In addition, by setting one or more of the oxidation reaction time, reaction temperature, and stirring conditions to (for example, extending the reaction time) a side where the oxidation proceeds more (i.e., a side with a higher degree of oxidation), there is a tendency to increase the zeta potential.
[0135] The nanocellulose in the first aspect can be subjected to hydrophobization. Hydrophobization can be carried out by forming an ester bond, a carbamate bond, an ether bond, etc. with the hydroxyl group on the surface of the nanocellulose, or by forming an ionic bond with a carboxyl group. The molecules used for hydrophobization are not particularly limited, and molecules with functional groups capable of forming the above-mentioned bonds can be used. Hydrophobization treatment can be carried out, for example, by hydrophobizing the nanocellulose obtained by defibrination in the (manufacturing method of the nanocellulose in the first aspect) described later.
[0136] (Method for producing nanocellulose in the first aspect)
[0137] The nanocellulose in the first aspect can be produced by defibrillating the above-mentioned oxidized cellulose. As a specific production method, for example, the method described in International Publication No. 2022 / 009979 and International Publication No. 2022 / 009980 can be cited. Nanocellulose can be obtained by defibrillating a commercially available product of oxidized cellulose (for example, AronFibro (registered trademark) manufactured by Toagosei Co., Ltd.).
[0138] <<Rubber ingredients>>
[0139] The rubber component used in the present invention refers to a component that is cross-linked to form rubber. The rubber component used in the present invention is not particularly limited, and a commercially available product can be used. It may be a synthetic rubber component or a natural rubber component.
[0140] Examples of the natural rubber component include chemically unmodified natural rubber polymers; chemically modified natural rubber polymers such as chlorinated natural rubber polymers, chlorosulfonated natural rubber polymers, and epoxidized natural rubber polymers; hydrogenated natural rubber polymers; and deproteinized natural rubber polymers.
[0141] Examples of the synthetic rubber component include diene rubber polymers such as butadiene rubber (BR) polymers, styrene-butadiene copolymer rubber (SBR) polymers, isoprene rubber (IR) polymers, acrylonitrile-butadiene rubber (NBR) polymers, chloroprene rubber (CR) polymers, styrene-isoprene copolymer rubber polymers, styrene-isoprene-butadiene copolymer rubber polymers, and isoprene-butadiene copolymer rubber polymers; and non-diene rubber polymers such as butyl rubber (IIR) polymers, ethylene-propylene rubber (EPM, EPDM) polymers, acrylic rubber (ACM) polymers, epichlorohydrin rubber (CO, ECO) polymers, fluororubber (FKM) polymers, silicone rubber (Q) polymers, urethane rubber (U) polymers, and chlorosulfonated polyethylene (CSM) polymers.
[0142] These rubber components may be used alone or in combination of two or more.
[0143] The rubber component may be in a solid state, a dispersion (latex) obtained by dispersing the rubber component in a dispersion medium, or a solution obtained by dissolving the rubber component in a solvent. The dispersion medium and the solvent may be, for example, water or an organic solvent. The amounts of the dispersion medium and the solvent may be 10 to 1000 parts by weight, respectively, relative to 100 parts by weight of the rubber component.
[0144] The rubber component in the present invention may be a rubber component before crosslinking, or may be a rubber component in which at least a part of the rubber component is crosslinked.
[0145] <<Method for producing rubber composition according to first aspect>>
[0146] The rubber composition of the first aspect can be produced, for example, by a production method including the step of mixing the nanocellulose of the first aspect with a rubber component, wherein the nanocellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and does not substantially contain an N-oxyl compound.
[0147] The oxidized cellulose in the first aspect used in the present invention is defibrated in the composition by a dispersion operation and a kneading operation during manufacture, thereby becoming nanocellulose. Specifically, the oxidized cellulose can be made into nanocellulose by mixing the oxidized cellulose with other materials contained in the rubber composition, performing a dispersion or kneading operation, and defibring the cellulose in the mixture, or by the manufacturer of the rubber composition defibring the cellulose by itself and making it micronized. The rubber composition of the first aspect of the present invention can be made using oxidized cellulose, which contains an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound.
[0148] One of the present inventions is a method for producing a rubber composition, the rubber composition comprising nanocellulose and a rubber component, the method comprising the following steps: obtaining the rubber composition by stirring a mixture comprising oxidized cellulose and a material other than the nanocellulose of the rubber composition, the oxidized cellulose comprising an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and substantially containing no N-oxyl compound.
[0149] In addition, one of the present inventions is a method for producing a rubber composition, the rubber composition comprising nanocellulose and a rubber component, the method comprising the steps of: obtaining the rubber composition by stirring oxidized cellulose and continuously adding materials other than the nanocellulose of the rubber composition, wherein the oxidized cellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and does not substantially contain an N-oxyl compound.
[0150] Here, aspects of nanocellulose, oxidized cellulose and rubber component are as described above. Materials other than nanocellulose of the rubber composition refer to any materials other than nanocellulose that may be contained in the rubber composition.
[0151] [Rubber composition: second aspect]
[0152] The rubber composition as one aspect of the present invention comprises nanocellulose and rubber component, and the above-mentioned nanocellulose has an anionic modified group, and the rubber component is grafted on the nanocellulose. The rubber composition is also referred to as the rubber composition of the second aspect. Grafting refers to that the molecular chain of the rubber component forms a chemical bond with the nanocellulose. As the above-mentioned chemical bond, it is preferably a covalent bond.
[0153] It should be noted that at least a portion of the rubber component contained in the rubber composition may be grafted onto the nanocellulose. Also, at least a portion of the nanocellulose contained in the rubber composition may be grafted onto the rubber component.
[0154] Here, grafting is considered to be a process in which free radicals are generated from the functional groups contained in the nanocellulose, namely the anionic modification groups and / or hydroxyl groups, and the double bonds in the rubber component are bonded, thereby forming an interaction between the nanocellulose and the rubber component. However, the form of grafting in the present invention is not limited thereto.
[0155] According to the rubber composition of the second aspect, the strength of the rubber, especially the tensile strength, can be improved in the same manner as the rubber composition of the first aspect. As a reason for improving the strength of the rubber, it is believed that by grafting the rubber component onto the nanocellulose, the affinity of the composite nanocellulose grafted with the rubber component and the rubber component is improved, and the composite nanocellulose is easily dispersed in the rubber component, and the strength, especially the tensile strength, is improved. The reason for the strength improvement is not limited to this.
[0156] <<Nanocellulose in the second aspect>>
[0157] The nanocellulose in the second aspect has an anion-modified group. In this specification, an anion-modified group refers to a group that generates anions. The anion-modified group is not particularly limited, and examples thereof include a carboxyl group, a phosphate group, a phosphite group, a sulfate group, a xanthate group, and the like.
[0158] For introducing anionic modification groups into nanocellulose, for example, it can be carried out by introducing anionic modification groups into cellulose raw materials, and then defibration to obtain nanocellulose with anionic modification groups, or by introducing anionic modification groups into nanocellulose, and the method is not limited. In addition, anionic groups can be introduced, for example, by converting a part of the cellulose structure into anionic modification groups, or by reacting a compound with anionic modification groups or a compound (also referred to as anionic modifier) that generates anionic modification groups by reacting with the cellulose structure to introduce anionic modification groups with the cellulose structure.
[0159] Nanocellulose having a carboxyl group can be obtained by, for example, oxidizing a cellulose-based raw material with an oxidizing agent to obtain oxidized cellulose having a carboxyl group, and then defibring the oxidized cellulose to obtain nanocellulose having a carboxyl group.
[0160] In addition, nanocellulose having a carboxyl group can be obtained, for example, by fibrillating carboxymethyl cellulose. Specifically, carboxymethyl cellulose can be obtained by mercerizing a cellulose raw material in the presence of a solvent and then performing an etherification reaction to obtain carboxymethyl cellulose. As a mercerizing agent, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be used. As a carboxymethylating agent, for example, sodium monochloroacetate can be used.
[0161] Furthermore, nanocellulose having a carboxyl group can also be obtained by, for example, reacting maleic acid or itaconic acid with commercially available nanocellulose.
[0162] Nanocellulose having a phosphate group can be obtained, for example, by reacting a cellulose-based raw material with a compound having a phosphate group, such as phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, ammonium metaphosphate, etc., to obtain cellulose having a phosphate group, and then defibrillating the cellulose having a phosphate group.
[0163] Nanocellulose having a phosphite group can be obtained, for example, by reacting a cellulose-based raw material with a phosphorus oxyacid (sodium hydrogen phosphate or sodium hydrogen phosphite) and urea, followed by defibration.
[0164] Nanocellulose having a sulfate group can be obtained, for example, by adding a cellulose raw material to a solution containing dimethyl sulfoxide (DMSO), acetic anhydride, and sulfuric acid to react, followed by defibration.
[0165] Nanocellulose having a xanthate group can be obtained, for example, by subjecting a cellulose raw material to an alkali treatment using an aqueous sodium hydroxide solution or the like as necessary, reacting the cellulose raw material with carbon disulfide, and then defibrating the resulting cellulose raw material.
[0166] As the anionic modifying group possessed by the nanocellulose in the second aspect, a carboxyl group is suitable. The nanocellulose having a carboxyl group is preferably a nanocellulose obtained by a manufacturing method including a TEMPO oxidation process and the above-mentioned <<Nanocellulose in the first aspect>>. The nanocellulose obtained by the manufacturing method including a TEMPO oxidation process can use a commercially available product, or can use nanocellulose manufactured according to Angew.Chem.Int.Ed.2021, 60, 24630-24636.
[0167] From the viewpoint of efficiency of grafting, the nanocellulose in the second aspect is more preferably the above-mentioned <<Nanocellulose in the first aspect>>. That is, the nanocellulose in the second aspect is more preferably a nanocellulose comprising an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and substantially free of N-oxyl compounds. By using a nanocellulose comprising an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and substantially free of N-oxyl compounds, as nanocellulose, the concentration of nanocellulose during grafting can be increased, and production efficiency can be improved. When the nanocellulose in the second aspect is a nanocellulose comprising an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and substantially free of N-oxyl compounds, the scheme is as described in the above-mentioned <<Nanocellulose in the first aspect>>.
[0168] The nanocellulose in the second aspect is a single fiber or an aggregate of the fiber. When the nanocellulose includes the nanocellulose with anionic modified groups, the aggregate of the fiber includes at least one nanocellulose with anionic modified groups, preferably the nanocellulose with anionic modified groups is the main component. Here, the nanocellulose with anionic modified groups is the main component and refers to the ratio of the nanocellulose with anionic modified groups to the total amount of nanocellulose to be greater than 50 mass %, preferably greater than 70 mass %, more preferably greater than 80 mass %. The upper limit of the above ratio is 100 mass %, but can be 98 mass %, can also be 95 mass %.
[0169] The average fiber length, aspect ratio and average fiber width of the nanocellulose in the second aspect are preferably the same as those of the nanocellulose in the first aspect. It should be noted that the average fiber length and average fiber width of the nanocellulose in the second aspect are the average fiber length and average fiber width of the nanocellulose before grafting.
[0170] The rubber component in the second aspect may be the same as the "Rubber component" in the first aspect.
[0171] The nanocellulose in the rubber composition of the second aspect has an anionic modification group, and the rubber component is grafted on the nanocellulose. Grafting can be performed by generating free radicals in the nanocellulose and reacting them with the rubber component, and the free radicals can be suitably generated by UV irradiation. That is, the composite nanocellulose grafted with the rubber component can be manufactured by a process of grafting the mixture of the nanocellulose and the rubber component by UV irradiation. One of the present inventions is a composite nanocellulose, which includes a rubber component and nanocellulose, the nanocellulose having an anionic modification group, and the rubber component is grafted to the nanocellulose.
[0172] <<Method for producing rubber composition according to second aspect>>
[0173] The rubber composition of the second aspect can be produced, for example, by a production method comprising the steps of mixing the nanocellulose of the second aspect, ie, nanocellulose having an anionic modifying group, with a rubber component to obtain a mixture, and irradiating the mixture with UV for grafting.
[0174] The above mixture may contain a dispersion medium. As a dispersion medium, there is no particular limitation as long as it is a dispersion medium that can disperse nanocellulose and / or rubber components and does not hinder grafting, and examples thereof include water, alcohols, ethers, ketones, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. As a dispersion medium, one of them may be used alone, or two or more thereof may be used in combination. Among the above dispersion media, as alcohols, methanol, ethanol, isopropanol, isobutanol, sec-butanol, tert-butanol, methyl cellosolve, ethylene glycol, and glycerol may be listed. As ethers, ethylene glycol dimethyl ether, 1,4-dioxane, and tetrahydrofuran may be listed. As ketones, acetone and methyl ethyl ketone may be listed. Of these dispersion media, water is preferred.
[0175] In order to remove oxygen that inhibits the generation of free radicals in the above-mentioned mixture, it is preferred to remove oxygen from the mixture. Removal of oxygen from the mixture can be performed by bubbling an inert gas.
[0176] The UV irradiation of the mixture can be performed using, for example, a high-pressure mercury lamp.
[0177] The temperature during UV irradiation is not particularly limited, and may generally be in the range of 0°C to 100°C, and may be 0°C to 70°C, or 10°C to 50°C.
[0178] In the rubber composition of the second aspect, when the nanocellulose of the first aspect is included, the rubber composition of the second aspect can be produced using the oxidized cellulose of the first aspect.
[0179] That is, one of the present inventions is a method for producing a rubber composition comprising composite nanocellulose grafted with a rubber component and a rubber component, comprising: a step of obtaining a mixture comprising nanocellulose and a rubber component by stirring a mixture comprising oxidized cellulose and a material other than nanocellulose of the rubber composition, and a step of grafting the mixture by UV irradiation, wherein the oxidized cellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and does not substantially contain an N-oxyl compound.
[0180] In addition, one of the present inventions is a method for producing a rubber composition comprising nanocellulose grafted with a rubber component and a rubber component, comprising: a step of obtaining a mixture comprising nanocellulose and a rubber component by stirring oxidized cellulose and continuously adding materials other than the nanocellulose of the rubber composition; and a step of grafting the mixture by UV irradiation, wherein the oxidized cellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and does not substantially contain an N-oxyl compound.
[0181] Here, the embodiments of nanocellulose, oxidized cellulose and rubber component are as described above. The material other than nanocellulose of the rubber composition refers to any material other than nanocellulose that can be contained in the rubber composition.
[0182] In the rubber compositions of the first and second aspects of the present invention, the ratio of each nanocellulose to the rubber component is not particularly limited. The nanocellulose is preferably in the range of 0.1 to 50 parts by mass, more preferably in the range of 0.1 to 30 parts by mass, further preferably in the range of 0.1 to 15 parts by mass, and even more preferably in the range of 0.5 to 15 parts by mass, relative to 100 parts by mass of the rubber component (solid content).
[0183] [rubber]
[0184] One of the present inventions is a rubber (a cross-linked product of a rubber composition) obtained by cross-linking the rubber composition of the present invention, i.e., the rubber composition of the first or second aspect. The rubber of the present invention can be obtained by heating the rubber composition of the present invention and / or adding a cross-linking agent to the rubber composition of the present invention.
[0185] In addition, when obtaining the rubber of the present invention, the rubber composition of the present invention may be kneaded in the presence of a crosslinking agent as required, and then crosslinked to obtain the rubber. This tends to further improve the strength of the rubber.
[0186] In the rubber of the present invention, when the rubber is the first rubber, it can be further kneaded with other rubber components to form a second rubber. That is, the rubber composition of the present invention can be used as a masterbatch and mixed with other rubbers and rubber components to obtain a rubber.
[0187] Examples of the crosslinking agent for obtaining the rubber of the present invention include sulfur, metal oxides, resin crosslinking agents, organic peroxides, and triazine derivatives, etc. These can be used alone or in combination of two or more.
[0188] Examples of sulfur include powdered sulfur, finely powdered sulfur, precipitated sulfur, colloidal sulfur, and sulfur chloride.
[0189] Examples of the metal oxide include magnesium oxide, calcium oxide, zinc oxide, and copper oxide.
[0190] Examples of the resin crosslinking agent include alkylphenol formaldehyde resins such as alkylphenol formaldehyde resins, heat-reactive phenolic resins, phenol diol-based resins, bisphenol resins, and heat-reactive bromomethyl alkylated phenolic resins.
[0191] Examples of the organic peroxide include alkyl peroxides, aryl peroxides, acyl peroxides, ketone peroxides, peroxyketals, peroxycarbonates, peroxyesters, and hydroperoxides. Specifically, dicumyl peroxide can be preferably used as the organic peroxide.
[0192] Examples of the triazine derivatives include 2,4,6-trimercapto-s-triazine, 2-methylamino-4,6-dimercapto-s-triazine, 2-(n-butylamino)-4,6-dimercapto-s-triazine, 2-octylamino-4,6-dimercapto-s-triazine, 2-propylamino-4,6-dimercapto-s-triazine, 2-diallylamino-4,6-dimercapto-s-triazine, 2-dimethylamino-4,6-dimercapto-s-triazine, 2-dibutylamino-4,6-dimercapto-s-triazine, and 2-(n-butylamino)-4,6-dimercapto-s-triazine. Amino-4,6-dimercapto-s-triazine, 2-di(isobutylamino)-4,6-dimercapto-s-triazine, 2-dipropylamino-4,6-dimercapto-s-triazine, 2-di(2-ethylhexyl)amino-4,6-dimercapto-s-triazine, 2-dioleylamino-4,6-dimercapto-s-triazine, 2-laurylamino-4,6-dimercapto-s-triazine or 2-anilino-4,6-dimercapto-s-triazine, or their sodium salts or disodium salts.
[0193] The amount of the crosslinking agent added may be appropriately adjusted and is usually in the range of 0.01 to 15 parts by mass, preferably 0.1 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the rubber component.
[0194] The temperature during cross-linking may be appropriately adjusted, and may generally be in the range of 20° C. to 200° C.
[0195] [Additives for rubber]
[0196] As described above, the rubber composition and rubber of the present invention can be obtained by mixing the oxidized cellulose in the first aspect and / or the nanocellulose in the first aspect into a rubber component. In addition, the rubber composition and rubber of the present invention can be obtained by mixing the composite nanocellulose grafted with a rubber component into a rubber component. That is, the oxidized cellulose in the first aspect, the nanocellulose in the first aspect, or the composite nanocellulose grafted with a rubber component of the present invention is an additive for rubber. It is preferred to add the oxidized cellulose in the first aspect, the nanocellulose in the first aspect, or the composite nanocellulose grafted with a rubber component of the present invention to reinforce the rubber, but the effect produced by the addition is not limited to this.
[0197] One of the present inventions is a rubber additive, which is a rubber additive containing oxidized cellulose, wherein the oxidized cellulose contains an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and substantially does not contain an N-oxyl compound. One of the present inventions is a rubber additive, which contains nanocellulose, wherein the nanocellulose contains an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and substantially does not contain an N-oxyl compound. One of the present inventions is a rubber additive, which contains composite nanocellulose grafted with a rubber component, wherein the nanocellulose is a nanocellulose having an anionic modified group.
[0198] The embodiments of the oxidized cellulose and nanocellulose used in the rubber additive of the present invention are the same as those in the above-mentioned <oxidized cellulose in the first aspect> and <nanocellulose in the first aspect>, respectively. The embodiment of the composite nanocellulose grafted with the rubber component is as described in the above-mentioned [Rubber composition: second aspect].
[0199] The properties of the rubber additive of the present invention are not particularly limited, and it can be liquid or solid. The rubber additive of the present invention can be in the form of a dried product of oxidized cellulose or (composite) nanocellulose, or a dispersion of oxidized cellulose or (composite) nanocellulose. In the case of a dispersion, it contains a dispersion medium that can disperse the oxidized cellulose or (composite) nanocellulose. There are no particular restrictions on the dispersion medium, and it can be appropriately selected according to the purpose. Specific examples of dispersion media include water, alcohols, ethers, ketones, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide. As a dispersion medium, one of them can be used alone, or two or more can be used in combination.
[0200] Among the above-mentioned dispersion media, alcohols include methanol, ethanol, isopropanol, isobutanol, sec-butanol, tert-butanol, methyl cellosolve, ethylene glycol, and glycerol. Ethers include ethylene glycol dimethyl ether, 1,4-dioxane, and tetrahydrofuran. Ketones include acetone and methyl ethyl ketone.
[0201] When the oxidized cellulose or (composite) nanocellulose is in the form of a dispersion, the concentration of the oxidized cellulose or (composite) nanocellulose in the dispersion may generally be in the range of 0.01 to 99% by mass. From the viewpoint of availability and handling, the concentration is preferably in the range of 0.5 to 50% by mass, more preferably in the range of 1 to 30% by mass, and even more preferably in the range of 1 to 20% by mass.
[0202] Example
[0203] Hereinafter, the present invention will be specifically described based on examples. It should be noted that the present invention is not limited to these examples. Hereinafter, unless otherwise specified, "parts" and "%" refer to parts by mass and mass %.
[0204] The methods for measuring the physical properties of nanocellulose and oxidized cellulose are as follows.
[0205] <Measurement method of fiber length and fiber width>
[0206] Pure water was added to the aqueous dispersion of fine cellulose fibers to adjust the concentration of fine cellulose fibers in the CNF aqueous dispersion to 5 ppm. The CNF aqueous dispersion after concentration adjustment was naturally dried on a mica substrate, and the shape of the fine cellulose fibers was observed in AC mode using a scanning probe microscope "MFP-3D infinity" manufactured by Oxford Asylum Co., Ltd.
[0207] The average fiber length was determined by binarization analysis of the obtained image using the image processing software "Image J". For more than 100 fibers, the number average fiber length was calculated according to fiber length = "circumference" ÷ 2.
[0208] The average fiber width was determined by using the software included with "MFP-3D infinity" for 50 or more fibers, based on the cross-sectional height of the shape image = fiber width, to obtain the number average fiber width [nm].
[0209] <Determination of carboxyl group content>
[0210] To 60 ml of an aqueous dispersion of oxidized cellulose having an oxidized cellulose concentration adjusted to 0.5% by mass was added a 0.1 M hydrochloric acid aqueous solution to adjust the pH to 2.5, and then a 0.05 N sodium hydroxide aqueous solution was added dropwise. The conductivity was measured until the pH reached 11.0, and the carboxyl group amount (mmol / g) was calculated using the following formula from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid whose conductivity changes relatively slowly.
[0211] Carboxyl group amount = a (ml) × 0.05 / mass of oxidized cellulose fiber (g)
[0212] [Production Example 1: Production of Oxidized Cellulose]
[0213] Pulp (KC Lock W100GK, Nippon Paper Industries, Ltd.) was used as the cellulose-based raw material.
[0214] 350 g of sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of 42% by mass were placed in a beaker, and pure water was added and stirred to obtain a sodium hypochlorite aqueous solution with an effective chlorine concentration of 21% by mass. 35% by mass hydrochloric acid was added thereto and stirred to a pH of 11.0. The sodium hypochlorite aqueous solution was stirred at 200 rpm using a propeller-type stirring blade in a stirrer (three-in-one motor, BL600) manufactured by Shinto Scientific Co., Ltd., while being kept at 30° C. in a constant temperature water bath, and then 50 g of the above-mentioned pulp was added.
[0215] After the addition of the cellulose raw material, a 48% by mass sodium hydroxide aqueous solution was added while being kept at 30° C. in the same constant temperature water tank, while maintaining the pH during the reaction at 11.0. The oxidation reaction was carried out for 4 hours in the above-mentioned stirrer while stirring at 60 rpm with three swept blades (continuing to maintain the pH).
[0216] After the reaction was completed, a filter cloth (manufactured by Nakao Filter Co., Ltd., KE022, air permeability 0.3 cc / cm 2 The product was separated into solid and liquid by filter pressing, and the obtained oxidized cellulose solid was washed with pure water. The carboxyl group content of the oxidized cellulose was 0.7 mmol / g.
[0217] In addition, the effective chlorine concentration in the sodium hypochlorite aqueous solution was measured by the following method.
[0218] (Determination of effective chlorine concentration in sodium hypochlorite aqueous solution)
[0219] Accurately weigh 0.582g of an aqueous solution of sodium hypochlorite pentahydrate crystals added to pure water, add 50mL of pure water, add 2g of potassium iodide and 10mL of acetic acid, cover tightly immediately, and place in dark for 15 minutes. After being placed for 15 minutes, free iodine (indicator starch test solution) was titrated with 0.1mol / L sodium thiosulfate solution (solution factor 1.000), and the titration amount was 34.55mL. In addition, blank test correction was carried out, and 1mL of 0.1mol / L sodium thiosulfate solution was equivalent to 3.545mgCl, so the effective chlorine concentration in the sodium hypochlorite aqueous solution was 21% by mass.
[0220] [Example 1]
[0221] The aqueous dispersion of oxidized cellulose (solid content 7.5%) obtained in Production Example 1 was treated with a homomixer (manufactured by Primix, Robomix) at 10,000 rpm and 300 mL of liquid for 46 minutes to fibrillate the oxidized cellulose into nanocellulose, thereby obtaining an aqueous dispersion of nanocellulose. The average fiber width was 3.7 nm, and the average fiber length was 150 nm.
[0222] 20 parts by mass of a nanocellulose aqueous dispersion was added to 100 parts by mass of a polybutadiene latex (Nipol LX111A2 manufactured by Zeon Japan, hereinafter referred to as "PB") of solid content, treated with a tabletop ultrasonic wave (MCS-6 manufactured by AS ONE) for 30 minutes, and dispersed with an ultrasonic homogenizer (LUH150 manufactured by Yamato Scientific) for 30 seconds. PB was added thereto to adjust the concentration of nanocellulose to 5 parts by mass, thereby obtaining a rubber composition.
[0223] The rubber composition was cast onto a release paper film and dried for 3 days at 50° C. The strength of the obtained rubber was tested in accordance with the <Strength Evaluation> described later.
[0224] [Example 2]
[0225] A nanocellulose aqueous dispersion was obtained in the same manner as in Example 1.
[0226] Relative to 100 parts by mass of PB of solid content, 20 parts by mass of nanocellulose aqueous dispersion were added, treated with a desktop ultrasonic wave (AS ONE manufactured, MCS-6) for 30 minutes, and dispersed for 30 seconds with an ultrasonic homogenizer (Yamato Scientific manufactured, LUH150). While stirring the dispersion obtained by the dispersion treatment, argon was bubbled at a flow rate of 100 mL / min for 30 minutes, and then UV irradiation (high pressure mercury lamp, Ushio SpotCure) was performed at 40°C for 90 minutes. PB was added thereto, and the concentration of nanocellulose was adjusted to 5 parts by mass to obtain a rubber composition.
[0227] The rubber composition was cast onto a release paper film and dried for 3 days at 50° C. The strength of the obtained rubber was tested in accordance with the <Strength Evaluation> described later.
[0228] [Comparative Example 1]
[0229] PB was cast onto a release paper film and dried for 3 days at 50° C. The strength of the obtained rubber was tested in accordance with the <Strength Evaluation> described later.
[0230] <Strength evaluation>
[0231] Strength evaluation was performed by the following tensile test.
[0232] The rubber obtained in Examples 1 to 2 and Comparative Example 1 was punched into test pieces (thickness: 1.5 mm) having a length of 5 mm and a width of 50 mm, and a tensile test was performed using a tensile tester (manufactured by INSTRON, INSTRON 5566A) at 23±2°C, a gauge length of 10 mm, and a tensile speed of 100 mm / min in accordance with JIS K6251.
[0233] The elastic modulus (Mpa), tensile strength (TS (MPa)), elongation at break (Eb (%)), 50% modulus (σ50 (MPa)), 300% modulus (σ300 (MPa)), and 800% modulus (σ800 (MPa)) were measured by tensile tests.
[0234] The results of the strength evaluation of the rubbers obtained in Examples 1 to 2 and Comparative Example 1 are shown in Table 1. In addition, the results of the measurement of the tensile stress / strain of the rubbers obtained in Examples 1 to 2 and Comparative Example 1 are shown in Table 1. Figure 1 .
[0235] [Table 1]
[0236]
[0237] [Example 3]
[0238] A nanocellulose aqueous dispersion was obtained in the same manner as in Example 1.
[0239] To 100 parts by weight of natural rubber latex (ULACOL manufactured by Regitex, solid content 61 wt%, hereinafter referred to as "NR") having a solid content, 5 parts by weight of a nanocellulose aqueous dispersion having a solid content was added, and the mixture was dispersed at 3000 rpm for 1 minute using a homomixer, and then dispersed by mixing at 2000 rpm for 1 minute and defoaming at 2200 rpm for 1 minute using a planetary agitator (Awatori Rentaro ARE310 manufactured by THINKY) to obtain a rubber composition.
[0240] The rubber composition was cast onto a plastic flat plate and air-dried at 60°C for 3 days to obtain a cast dried product.
[0241] The cast dried product was plasticized at 70°C and 60 rpm for 5 minutes using a batch melt kneader (Labo Plastomill 10S100, mixer R60, Banbury blade, manufactured by Toyo Seiki Seisaku-sho, Ltd.), 2 parts by mass of a cross-linking agent (PERCUMYL D (also known as DCP) manufactured by NOF Corporation) was added, and kneading was continued for 10 minutes to obtain a kneaded product.
[0242] The kneaded product was placed in a 1 mm thick mold, sandwiched between SUS plates, and subjected to a heat press at 165°C, 20 MPa, and 20 minutes to perform a crosslinking reaction and molding to obtain a sheet of rubber. The strength of the obtained sheet of rubber was tested according to <Strength Evaluation> described below.
[0243] [Example 4]
[0244] A nanocellulose aqueous dispersion was obtained in the same manner as in Example 1.
[0245] The rubber and nanocellulose were mixed in the same manner as in Example 2 except that the raw material was NR, and the concentration of the nanocellulose was adjusted to 5 parts by mass to obtain a rubber composition.
[0246] The rubber composition was cast onto a plastic flat plate and air-dried at 50°C for 3 days to obtain a cast dried product.
[0247] The cast dried product was batch-melted and kneaded in the same manner as in Example 3, and then molded. The strength of the obtained sheet rubber was tested in accordance with <Strength Evaluation> described later.
[0248] [Example 5]
[0249] When attempting to obtain a rubber composition in the same manner as in Example 4 except that nanocellulose obtained by TEMPO oxidation was used as the nanocellulose aqueous dispersion, grafting could not be performed due to the excessive viscosity of the nanocellulose aqueous dispersion. Therefore, when nanocellulose obtained by TEMPO oxidation was used, the CNF concentration needed to be diluted to 0.2% to obtain a rubber composition in the same manner as in Example 4.
[0250] The rubber composition was cast onto a plastic flat plate and air-dried at 50°C for 3 days to obtain a cast dried product.
[0251] The cast dried product was batch-melted and kneaded in the same manner as in Example 3, and then molded. The strength of the obtained sheet rubber was tested in accordance with <Strength Evaluation> described later.
[0252] It should be noted that the nanocellulose obtained by TEMPO oxidation is obtained by manufacturing according to Angew.Chem.Int.Ed.2021, 60, 24630-24636.
[0253] [Comparative Example 2]
[0254] NR was cast onto a plastic flat plate and dried at 50°C for 3 days. The cast dried product was batch melt kneaded and hot pressed in the same manner as in Example 3 to obtain a sheet rubber. The strength of the obtained sheet rubber was tested in accordance with <Strength Evaluation> described later.
[0255] [Comparative Example 3]
[0256] A rubber composition was obtained in the same manner as in Example 3, except that nanocellulose obtained by TEMPO oxidation was used as the nanocellulose aqueous dispersion.
[0257] The rubber composition was cast onto a flat plate made of plastic and air-dried at 50°C for 3 days to obtain a cast dried product.
[0258] The cast dried product was batch-melted and kneaded in the same manner as in Example 3, and then molded. The strength of the obtained sheet rubber was tested in accordance with the <Strength Evaluation> described later.
[0259] [Comparative Example 4]
[0260] When an attempt was made to obtain a rubber composition in the same manner as in Example 3 except that nanocellulose obtained by mechanical defibration was used as the nanocellulose aqueous dispersion, grafting could not be performed due to the excessively high viscosity of the nanocellulose aqueous dispersion.
[0261] It should be noted that the nanocellulose obtained by mechanical defibration was produced in accordance with page 40 of "Raw Material Evaluation Book for Promotion of CNF Utilization".
[0262] <Strength evaluation>
[0263] Dumbbell-shaped test pieces (thickness: 1.1 to 1.4 mm) with a total length of 75 mm and a gauge width of 2 mm were prepared from the rubbers obtained in Examples 3 to 5 and Comparative Examples 2 and 3. The samples were subjected to a tensile test in accordance with JIS K6251 at 23±2°C, a gauge length of 20 mm, and a tensile speed of 500 mm / min using a tensile testing machine (manufactured by INSTRON, INSTRON 5566A).
[0264] The elastic modulus (MPa), tensile strength (TS (MPa)), elongation at break (Eb (%)), 50% modulus (σ50 (MPa)), 300% modulus (σ300 (MPa)), and 800% modulus (σ800 (MPa)) were measured by tensile tests.
[0265] The results of strength evaluation of the rubbers obtained in Examples 3 to 5 and Comparative Examples 2 and 3 are shown in Table 2. In addition, the results of measurement of tensile stress / strain of the rubbers obtained in Examples 3 to 5 and Comparative Examples 2 and 3 are shown in Table 2. Figure 2 .
[0266] [Table 2]
[0267]
Claims
1. A rubber composition comprising nanocellulose and a rubber component, The nanocellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound.
2. A rubber composition comprising nanocellulose and a rubber component, The nanocellulose has an anionic modified group, The rubber component is grafted onto the nanocellulose.
3. A rubber composition comprising nanocellulose and a rubber component, The nanocellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and substantially does not contain an N-oxyl compound. The rubber component is grafted onto the nanocellulose. 4 . A rubber obtained by crosslinking the rubber composition according to claim 1 .
5. A method for producing a rubber composition, the rubber composition comprising nanocellulose and a rubber component, The manufacturing method comprises the steps of: stirring a mixture containing oxidized cellulose and a material other than the nanocellulose of the rubber composition, defibring the oxidized cellulose, and obtaining the rubber composition; The oxidized cellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound.
6. A method for producing a rubber composition, the rubber composition comprising nanocellulose and a rubber component, The manufacturing method comprises the following steps: stirring oxidized cellulose, defibrating the oxidized cellulose, and continuously adding materials other than the nanocellulose of the rubber composition to obtain the rubber composition, The oxidized cellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound. 7 . The production method according to claim 5 , further comprising a step of grafting the nanocellulose onto the rubber component.
8. A rubber additive comprising nanocellulose, The nanocellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound.
9. A rubber additive comprising oxidized cellulose, The oxidized cellulose includes an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof, and does not substantially contain an N-oxyl compound.
10. A composite nanocellulose comprising a rubber component and nanocellulose, The nanocellulose has an anionic modified group, The rubber component is grafted to the nanocellulose.
11. A composite nanocellulose comprising a rubber component and nanocellulose, The nanocellulose comprises an oxide of a cellulose-based raw material obtained using hypochlorous acid or a salt thereof and substantially does not contain an N-oxyl compound. The rubber component is grafted to the nanocellulose.
12. A rubber additive comprising the composite nanocellulose according to claim 10 or 11.
